Broadened ferromagnetic resonance range in ferrite by gradient composition design. Issue 18 (15th December 2019) - Liu, Chuyang; Cao, Yufan; Zhang, Xiaohan; Ren, Hao; Zhang, Yujing; Zhang, Yanting; Zhao, Xinrui; Fang, Gang; Peng, Kangsen; Zou, Junding
Abstract: Magnetic materials with broad ferromagnetic resonance (FMR) range have great potential in microwave absorption field. In this work, M type barium ferrites with local chemical gradients were prepared by mixing and heating the ferrite powders with different Zr 4+ -Ni 2+ contents, constructing the locally inhomogeneous magnetocrystalline anisotropy field to widen the FMR range. The results show that ionic diffusion process starts significantly at 1000 °C. The mixed ferrite reheated at 1100 °C finally exhibits the broadest FMR range (7.32 GHz) because of the appropriate gradient composition design, which is much wider than that of the original uniformly substituted barium ferrites.